Intralaminar fracture of unidirectional carbon/epoxy composite: experimental results and numerical analysis. (15th May 2016) - Pappas, G.; Botsis, J.
Abstract: Fracture of carbon fiber reinforced polymers (CFRPs) is dominated by large scale fiber bridging which acts as a very important toughening mechanism. The objective of this paper is to investigate the intralaminar Mode I fracture in a unidirectional CFRP composite in double cantilever beam specimens with thickness H  = 6, 10 and 14 mm with a symmetric intralaminar precrack introduced by a thin diamond wire saw. Optical fibers with 10 multiplexed Bragg grating sensors are glued onto the upper surface of selected specimens of H  = 6 and 10 mm, to measure the axial strain profile during fracture. The bridging tractions are expressed as a function of the maximum bridging stress, the bridging zone length and exponential softening parameter. The measured strains are input to an inverse parametric numerical model to obtain the traction separation relation due to bridging. The optimized strain distribution corresponds to a bridging traction profile, with a maximum bridging traction of ∼8.3 MPa. This stress is 6 times larger than the corresponding in interlaminar fracture value. The resultant resistance-curves increase with sample thickness in corresponding steps of 20%. The plateau energy release rate is ∼2.3 times higher than the corresponding interlaminar one, although having the same initial fracture toughness. The calculated energy contribution of bridging agrees very well with the produced resistance-curves. The resultant bridging law is applied over a cohesive element model to reproduce the load-displacement curves.